Evaluation on gas production potential from laminar hydrate deposits in Shenhu Area of South China Sea through depressurization using vertical wells - Su, Zheng; He, Yong; Wu, Nengyou; Zhang, Keni; Moridis, George J. (Journal of Petroleum Science and Engineering, 2012)
Gas hydrates are solid crystalline compounds in which gas molecules are lodged in lattices of ice crystals. Shenhu area is considered as one of the most promising fields on north continental slope of the South China Sea (SCS). Drilling and sampling at the site has indicated occurrences of methane hydrate in clay silty sediments. The thin Hydrate-Bearing Layer (HBL) is overlain and underlain by zones of mobile water, and the layer does not appear to be bounded by low-permeability strata. In this study we assess by means of numerical simulation the production potential of the laminar hydrate deposit at drilling site SH3 in the Shenhu area. We simulate the hydrate dissociation and the gas production induced by depressurization at a vertical well. To minimize gas losses through the overburden and excessive water production through proximity to the permeable, water-saturated zones, a perforated interval is limited to the middle section of the vertical well within the hydrate layer. The simulations show that productions from depressurization-induced dissociation through a vertical well at constant well pressure do not appear to be a promising approach in the deposits of low hydraulic diffusion. The production of hydrate-originating gas decreases at the beginning of the production and then keep stable in the reference case and the average production is 211 m(3)/d. The deposit permeability is considered as the most insensitive parameter to enhance the gas production. And the production potential is much lower than that of deposits having an impermeable upper boundary as expectation. (C) 2012 Elsevier B.V. All rights reserved.